(untitled) (Faculty of Education Scientific Journal, 2024)
Christianity found slaves without value in the pagan society, so it tried to take care of them and sensing them with their humanity, but it did not try to abolish slavery or even prevent it. The enemies of Christianity took advantage of the sympathy of the church to the poor and the slaves. Where Celsus said sarcastically that Christians accept among them children, fools, and and persons devoid of perception, and slaves whenever they are renewed. Origen replied to him saying: We do not reject anyone, not even the slave, Christianity is for all people, we only give them attention, hoping to make them in a better situation. Christianity paid attention to slaves and gave them great importance in the early Christianity, and treated them gently, but despite the fact that the Roman state issued some laws to encourage emancipation and prevent slavery, This research aims to display the real reasons behind preventing the emancipation of believing slaves in the Christian community. The Church did not attempt to prevent or reduce slavery, and instead eased the conditions of slaves, and it made them brothers in God, and tried to justify slavery by making it a human nature and a divine punishment, and the believers must be patient until that divine punishment is lifted by real repentance.